Erythropoietin Mitigates Diabetic Nephropathy by Restoring PINK1/Parkin-Mediated Mitophagy - Yi, Xinyao; Yan, Wenhui; Guo, Tingli; Liu, Na; Wang, Zhuanzhuan; Shang, Jia; Wei, Xiaotong; Cui, Xin; Sun, Yuzhuo; Ren, Shuting; Chen, Lina (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN), one of the most detrimental microvascular complications of diabetes, is the leading cause of end-stage renal disease. The pathogenesis of DN is complicated, including hemodynamic changes, inflammatory response, oxidative stress, among others. Recently, many studies have demonstrated that mitophagy, especially PINK1/Parkin-mediated mitophagy, plays an important role in the pathogenesis of DN. Erythropoietin (EPO), a glycoprotein hormone mainly secreted by the kidney, regulates the production of erythrocytes. This research intends to explore the beneficial effects of EPO on DN and investigate related mechanisms. In vitro experiments, we found that EPO promoted autophagic flux and alleviated mitochondrial dysfunction in terms of mitochondrial fragmentation, elevated mitochondrial ROS as well as the loss of mitochondrial potential, and lowered the apoptosis level in high-glucose-treated mesangial cells. Moreover, EPO increased protein expressions of PINK1 and Parkin, enhanced the co-localization of LC3 with mitochondria, Parkin with mitochondria as well as LC3 with Parkin, and increased the number of GFP-LC3 puncta, resulting in increased level of PINK1/Parkin-mediated mitophagy in mesangial cells. The knockdown of PINK1 abrogated the effect of EPO on mitophagy. In addition, in vivo experiments demonstrated that EPO attenuated renal injury, reduced oxidative stress, and promoted expressions of genes related to PINK1/Parkin-mediated mitophagy in the kidneys of DN mice. In summary, these results suggest that PINK1/Parkin-mediated mitophagy is involved in the development of DN and EPO mitigates DN by restoring PINK1/Parkin-mediated mitophagy.